2006
DOI: 10.1091/mbc.e05-10-0913
|View full text |Cite
|
Sign up to set email alerts
|

The Ras-GRF1 Exchange Factor Coordinates Activation of H-Ras and Rac1 to Control Neuronal Morphology

Abstract: The Ras-GRF1 exchange factor has regulated guanine nucleotide exchange factor (GEF) activity for H-Ras and Rac1 through separate domains. Both H-Ras and Rac1 activation have been linked to synaptic plasticity and thus could contribute to the function of Ras-GRF1 in neuronal signal transduction pathways that underlie learning and memory. We defined the effects of Ras-GRF1 and truncation mutants that include only one of its GEF activities on the morphology of PC12 phaeochromocytoma cells. Ras-GRF1 required coexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 79 publications
(145 reference statements)
1
21
0
2
Order By: Relevance
“…These pathways may also contribute to ROS production. Of interest, RAC1 may be downstream of RAS, 57 and we have previously shown that RAS activation leads to ROS production via RAC1. 44 Thus, other signaling pathways may also contribute to ROS production and genomic instability in FLT3/ITD-positive AML.…”
Section: Discussionmentioning
confidence: 99%
“…These pathways may also contribute to ROS production. Of interest, RAC1 may be downstream of RAS, 57 and we have previously shown that RAS activation leads to ROS production via RAC1. 44 Thus, other signaling pathways may also contribute to ROS production and genomic instability in FLT3/ITD-positive AML.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria were harvested and lysed by sonication on ice in 50 mM Tris-Cl (pH 8.0), 150 mM NaCl, 0.2% sodium deoxycholate, and 0.1% Triton X-100. The lysate was cleared by centrifugation, and RNF8 prebound glutathione-Sepharose beads were prepared according to protocol as described previously (21). FLAG-ATDC was in vitro translated directly from the PCR products that contain the T7 promoter by TNT quick coupled transcription/translation system according to manufacturer's protocol (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…These results prompted us to examine whether a particular downstream signaling pathway that is coupled to NR1NR2B-containing receptors is required to induce dendritic branch development. Given that RasGRF1 is a key signaling component in the regulation of several forms of neuronal plasticity, specifically associates with the NR2B subunit (Krapivinsky et al 2003;Li et al 2006), and controls neurite extension in PC12 cells (Yang and Mattingly 2006), we hypothesized that the binding of RasGRF1 to NMDARs is necessary for inducing branch formation. To impede the interaction between the NR2B subunit and RasGRF1, VSCNs were transfected with DsRed2 and NR2B (Fig.…”
Section: Disruption Of Nr2b-rasgrf1 Interaction Inhibits Dendritic Brmentioning
confidence: 99%